An Epistemological Appraisal of Walton’s Argument Schemes - Lumer, Christoph (Informal Logic)

(untitled) (Informal Logic, 2022)
The article critically discusses Walton’s (and co-authors’) argument scheme approach to good argumentation. Four characteristics of Walton’s approach are presented: 1. Argument schemes provide normative requirements. 2. These schemata are enthymematic. 3. There are associated critical questions. 4. The method is inductive, abstracting schemata from groups of similar arguments. Four adequacy conditions are applied to these characteristics: AC1: effectiveness in achieving the epistemic goal of obtaining and communicating justified acceptable opinions; AC2: completeness in capturing the good argument types; AC3: efficiency in achieving the goals; AC4: justification of the argument schemes. The discussion reveals weaknesses in Walton’s account, including they are neither effective nor truly justified. A better alternative is an epistemological approach based on epistemological principles.